Salidroside Inhibits CCl4-Induced Liver Fibrosis in Mice by Reducing Activation and Migration of HSC Induced by Liver Sinusoidal Endothelial Cell-Derived Exosomal SphK1 - Ye, Qiannan; Zhou, Yang; Zhao, Changqing; Xu, Lieming; Ping, Jian (Frontiers in Pharmacology, 2021)
Sphingosine kinase 1 (SphK1) / Sphingosine-1-phosphate (S1P)/S1PRs signaling pathway is known to involve the advancement of liver fibrosis. Exosomal SphK1 promotes hepatic stellate cells (HSC) migration. Salidroside (Sal) inhibits liver fibrosis, but its mechanism is yet to be elucidated. This study was to explore the influences of Sal on the SphK/S1P/S1PRs signaling pathway in liver fibrosis induced by carbon tetrachloride (CCl4) in vivo, and investigated the mechanism of Sal affecting the migration and activation of HSC triggered by exosomal SphK1 in vitro. Our data showed that Sal reduced the activities of alanine transaminase (ALT), aspartate aminotransferase (AST) in serum, and hydroxyproline (Hyp) content in the liver tissue. Sal subdued the expression of α-smooth muscle actin (α-SMA), fibronectin (FN) and type I collagen (Col I) of the liver. Sal also reduced mitochondria-induced hepatocyte apoptosis and to inhibit JNK activation. Furthermore, Sal remarkably eradicated the influence of SphK1, SphK2, S1P, and S1PRs triggered by CCl4, whether stimulating or hindering. Compared with serum-derived exosomes from model group mice, serum-derived exosomes from Sal group mice expressed lower SphK1 and reduced JS 1(mouse HSC cell line) migration. In addition, Sal was also observed to subdue Col I expression, AKT activation, and LX-2 migration induced by exosomal SphK1 from SK-HEP-1 (a kind of liver sinusoidal endothelial cells (LSEC) cell line). In conclusion, Sal could effectively alleviate liver injury, hepatocyte apoptosis, and liver fibrosis in vivo, providing supports that the protective effects of Sal might be realized by suppressing JNK activation and modulating the SphK/S1P/S1PRs axis. In vitro, it was observed that Sal might alleviate LX-2 migration and activation induced by exosomal SphK1 by inhibiting the AKT activation.